2021
DOI: 10.1101/2021.01.11.21249579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological Legacies of Intergenerational Trauma under South African Apartheid: Prenatal Stress Predicts Increased Psychiatric Morbidity during Late Adolescence and Early Adulthood in Soweto, South Africa

Abstract: BackgroundSouth Africa’s rates of psychiatric morbidity are among the highest in sub-Saharan Africa and are foregrounded by the country’s long history of political violence during apartheid. Recent evidence suggests that maternal trauma during gestation may intergenerationally impact the developing fetus and elevate the future child’s risk for psychiatric disease. We aim to evaluate the intergenerational effects of prenatal stress experienced during apartheid on late adolescent psychiatric morbidity and also a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…After 13 months in inadequate evacuation camps, adjusting to a new environment may have been stressful. Consistent with other research, it has been discovered that prolonged stress has the most detrimental impacts on children, such as altering brain chemistry and function and decreasing illness resistance (Battaglia et al, 2023;Green et al, 2021;Kim et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…After 13 months in inadequate evacuation camps, adjusting to a new environment may have been stressful. Consistent with other research, it has been discovered that prolonged stress has the most detrimental impacts on children, such as altering brain chemistry and function and decreasing illness resistance (Battaglia et al, 2023;Green et al, 2021;Kim et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…A study found that younger children are more susceptible to the adverse effects of unfamiliar environments and stress (Karam et al, 2019). According to a different study, children under the age of ten who were born preterm, had temperaments that were "difficult" or "slow-to-warm-up," were male, had low cognitive function, or had experienced prenatal stress suffered worse from stress (Kim et al, 2021;Shawi, 2016). On a side note, seven of the eight children in this study with elevated stress levels were older than ten.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if behaviour change intervention efforts intend to promote nurturing care of young children in the next generation, then it is imperative that intervention strategies are realistic about how context can hinder the provision of such care. Attention also needs to be paid to how these strategies can contribute to breaking cycles of intergenerational trauma, which have already been identified in Soweto (Kim et al, 2021), and in South Africa more generally where many historic legacies of apartheid persist (Gobodo--Madikizela, 2016). Acknowledgement of higher-level drivers of trauma has been recognised as one of the guiding principles of a trauma-informed approach, specifically cultural, historical and gender issues (Centers for Disease Control and Prevention, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing engagement with epigenetics as an explanatory framework for the health disparities faced by Indigenous communities in South Africa and across North America. These communities also experience a disproportionate burden of disease, as well as historical trauma which has been associated with subsequently high rates of substance abuse, depression, post-traumatic stress and suicide, and high rates of adverse childhood experiences (ACEs) (Brockie et al, 2013;Bombay et al, 2011Bombay et al, , 2014Kim, 2020;Pentecost et al, 2018;Phillips-Beck et al, 2018). Many communities have signalled interest in epigenetics as a framework for understanding the intergenerational transmission of these health challenges as it is culturally relevant and resonates with Indigenous understandings of historical trauma and ancestral memory (Brockie et al, 2013;Bombay et al, 2014;Thunderbird Partnership Foundation, 2019;Warin et al, 2020).…”
Section: The Global Context: Black and Indigenous Engagements With Ep...mentioning
confidence: 99%